(3eWGdY GdCfXGQ aj TQM WhGdY GdCfhGQ aj GdcdGe Yf eJf GdHjVGhjs - (3eMehO Hf YHO GdQMef Hf CMeO Hf eMeO, CHh GdKfGA, TeS GdOjf GdCUagGfj, Ch GdCUHgGfj ,J (B749 (3g` s ((3eMeO Hf Ydi GdHdHjSj GdTGaYj s)
(3ChdgG (B:s
(3GdMeO ddg GdPj JhMO HhLhH GdhLhO hOhGe GdHbGA (B, (3GeG HYO aEf GQHGH GdYbd eJWGHbhf hGUMGH Gdfbd eJhGabhf s
(3BNQgG (B:s
(3aef jDef HGddg hQShdg Udj Gddg Ydjg hSde cja jLhR Cf jHZV ef gh ehUha HgPg GdUaGJ s
(3GdfSNI HgG MhGTs
(3HBNQg ELGRI GdMUcaj dTeS GdOjf eMeO NWIs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3eJaQbGJs